2015
DOI: 10.2174/1389450116666150113121054
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Mediated DNA Methylation Pattern Alterations in Carcinogenesis

Abstract: Elevated levels of both reactive oxygen species (ROS) and DNA methylation are characteristic of various types of cancer cells. However, the relation between these two is not well understood. Here we will discuss the cause-consequence relationship between ROS and DNA methylation. Cancer research reveals that disregulation of DNA methylation results in regional CpG island hypermethylation and generalized genomic hypomethylation. ROS-induced oxidative stress is associated with both aberrant hypermethylation of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
164
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(169 citation statements)
references
References 0 publications
5
164
0
Order By: Relevance
“…49 Elevated ROS levels are known to induce site-specific alterations in DNA methylation by mechanisms such as modulation of the expression of DNA methyltransferases (DNMTs). 50 While the observed gene-specific changes in DNA methylation are likely to be directly induced by morphine administration, global changes in 5-mc and 5-hmc content could in part be non-specific effects through increased ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…49 Elevated ROS levels are known to induce site-specific alterations in DNA methylation by mechanisms such as modulation of the expression of DNA methyltransferases (DNMTs). 50 While the observed gene-specific changes in DNA methylation are likely to be directly induced by morphine administration, global changes in 5-mc and 5-hmc content could in part be non-specific effects through increased ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the cellular redox status are implicated in the regulation of epigenetic processes contributing to the development and progression of cancer [221223]. One such epigenetic modification is DNA methylation, which is tightly regulated by the action of DNA methyltransferases enzymes such as DNMT1, DNMT3A and DNMT3B [224].…”
Section: Redox Regulation Of Epigeneticsmentioning
confidence: 99%
“…Previously, there have also been studies proving the role of DNMT1 in addressing the possible influence of elevated oxidative stress on genome-wide DNA methylation levels [40]. Wu et al reported that reactive oxygen species might induce site-specific hypermethylation via either the overexpression of DNMTs or the formation of a new DNMT-containing complex that better catalyzes this modification [41]. Our study discovered that, compared to LECs from ARC cases, LECs from HMC cases showed higher expression of DNMT1 at both the mRNA and protein levels, where the LECs were in a condition with higher levels of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%